Bacterial contamination of Ugandan paper currency notes possessed by food vendors around Mulago Hospital complex, Uganda - Allan, Muhumuza; Atuhaire, Catherine; Nathan, Musisi; Ejobi, Francis; Cumber, Samuel Nambile (Pan African Medical Journal, 2018)
Introduction: Paper currency notes, exchangeable fomite, that is continuously contaminated because of the poor handling and storage practices. Objective: the general objective of the study was to determine the bacterial contamination of paper currency notes possessed by food vendors around Mulago National Referral Hospital Complex. Methods: A total of sixty paper notes of six denominations (1000, 2000, 5000, 10000, 20000, 50000) were collected from different food vendors. Each note was preserved in a sterile falcon tube and transported to the microbiology lab for bacteriological examination. Data from questionnaires was analyzed using SPSS version 23 (IBM SPSS Statistics). Results: All sampled paper notes had bacterial contamination. The bacterial counts ranged from 4×102cfu/ml to 6.8×109 cfu/ml, with the Shs.1000 notes having the highest average total bacterial load of 2.17×109 cfu/ml and highest average total coli form counts of 21.5×102 cfu/ml. The fifty thousand shillings note had no coliform detected. Of the analysed 60 samples, 27(45%) samples contained Staphylococcus aureus. None of the sampled paper notes had Escherichia coli. Conclusion: The study revealed that most of Ugandan paper notes are contaminated with bacteria including potential pathogens that cause disease in healthy individuals and opportunistic pathogens that may cause disease in hospitalized and immunocompromised patients. This study showed that the most contaminated note denominations were those of low denomination (Shs.1000 and Shs.2000) which had the highest bacterial count. The study revealed the paper currency notes were stored in different places where the commonest was the drawer and kept with different items, the commonest being pens. Hence, great care must be taken while handling money during the preparation and handling of food to avoid cross contamination
Keywords: Bacterial contamination; Pathogens; Food vendors; Escherichia coli; Staphylococcus aureus; Paper notes